2015
DOI: 10.1128/iai.02457-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Detergent on Biophysical Properties and Immune Response of the IpaDB Fusion Protein, a Candidate Subunit Vaccine against Shigella Species

Abstract: c Shigella spp. are causative agents of bacillary dysentery, a human illness with high global morbidity levels, particularly among elderly and infant populations. Shigella infects via the fecal-oral route, and its virulence is dependent upon a type III secretion system (T3SS). Two components of the exposed needle tip complex of the Shigella T3SS, invasion plasmid antigen D (IpaD) and IpaB, have been identified as broadly protective antigens in the mouse lethal pneumonia model. A recombinant fusion protein (DB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…S1A, S2A, and S3A). Thus, as seen previously for a fusion protein consisting of Shigella IpaD (tip protein) and IpaB (called DB fusion or DBF), the presence of LDAO seemed to have a stabilizing effect at low pH for the translocator proteins.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…S1A, S2A, and S3A). Thus, as seen previously for a fusion protein consisting of Shigella IpaD (tip protein) and IpaB (called DB fusion or DBF), the presence of LDAO seemed to have a stabilizing effect at low pH for the translocator proteins.…”
Section: Resultssupporting
confidence: 62%
“…The translocator proteins IpaB, SipB, and YopB were coexpressed with their chaperones that were removed with the detergent LDAO . The biophysical characterization of these proteins was conducted in the presence of LDAO to maintain each protein's solubility.…”
Section: Resultsmentioning
confidence: 99%
“…Some T3SS proteins are surface-exposed and can be targeted by neutralizing antibodies. The T cell response to T3SS antigens was recently shown to be associated with protection against C. trachomatis infection in highly exposed women [13], and T3SS components have recently attracted attention as vaccine candidates against other pathogenic bacteria [1417]. The C. trachomatis T3SS filament protein, CdsF, and its orthologs in other bacteria form the needles of injectisomes and are believed to facilitate the insertion of translocators into the host cell membrane [11, 12, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LDAO is an inexpensive, generally regarded as safe (GRAS) detergent that is effective at low levels and has been included in the successful formulation of Shigella vaccines containing a novel IpaD/IpaB fusion complex already. 22,28 Determining the impact of a vaccine a priori is difficult, though the findings presented here together with previous vaccine studies involving Shigella T3SA tip proteins and the detergent LDAO suggest that a vaccine including IpaC-LDAO is not only feasible, but may provide a valuable addition to the currently available antigens used in anti- Shigella vaccine formulation.…”
Section: Discussionmentioning
confidence: 83%
“…22–27 The Picking lab at the University of Kansas has recently characterized both IpaD and IpaB as pan- Shigella vaccine candidates finding that each provided significant protection when tested using a murine pulmonary infection model, 23 leading to the development of a novel IpaB-IpaD fusion complex that resulted in similar levels of protection and enhanced cytokine responses. 22,28 While the tip proteins IpaD and IpaB are proving to be valuable vaccine components, pioneering Shigella immunogenicity studies showed that IpaC generates a strong immunogenic response during Shigella infections, 8 driving the development of promising multicomponent Shigella vaccines containing IpaC 26,27,29 as well as preliminary studies using urea-isolated IpaC. 25 Despite these advances, however, challenges obtaining and stabilizing recombinant IpaC have thus far prevented necessary vaccine formulation and full characterization of its efficacy.…”
Section: Introductionmentioning
confidence: 99%